2022
DOI: 10.3390/fermentation8060248
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Anthocyanin-Rich Black Cane (Saccharum sinensis Robx.) Silage for Ruminants Using Molasses and Iron Sulphate: A Sustainable Alternative

Abstract: Anthocyanin-rich black cane (aBC) is a grass rich in lignin and carbohydrates, with an abundance of anthocyanins. Silages of aBC produced with molasses (MS) and/or ferrous sulphate (FS) mixtures may have beneficial effects on silage quality and animal performance in ruminants. However, the addition of MS and FS to ensiled grass is relatively unexplored. Therefore, this study systematically evaluated the effect of their administration at different doses to select an effective treatment to modulate the ensiling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Ensiling has been proposed as an efficient method of preserving roughage in light of the fact that such agricultural activities pose a significant disposal problem, e.g., decomposition or open burning. However, it necessitates a suitable effort prior to ensiling because the breakdown of biomass during anaerobic fermentation results in functional microorganisms and chemicals that reduce nutrient loss in addition to harmful substances ( 1 ). Using iron dilutions can help significantly with forage preservation ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ensiling has been proposed as an efficient method of preserving roughage in light of the fact that such agricultural activities pose a significant disposal problem, e.g., decomposition or open burning. However, it necessitates a suitable effort prior to ensiling because the breakdown of biomass during anaerobic fermentation results in functional microorganisms and chemicals that reduce nutrient loss in addition to harmful substances ( 1 ). Using iron dilutions can help significantly with forage preservation ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the highly lignified components of anthocyanin-rich black cane reduce the bioaccessibility of anthocyanin during rumen feeding. In addition, earlier studies demonstrated that the incorporation of anthocyanin-rich black cane with dilutions of FSH at levels ranging from 0.015 to 0.030% on fresh weight (FW) into anthocyanin-rich black cane silages improved the nutritional balance with massively decreased lignin contents, as well as modulated anthocyanin stability during ensiling, and in vitro ruminal fermentation of anthocyanin-rich black cane silages ( 1 , 2 ). These findings support the notion that using those FSH levels might aid the current study in terms of decreasing the lignin content of anthocyanin-rich black cane silages prior to feeding.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations